University-led intellectual property commercialization: Cases of Malaysian universities - Sharif S.M.; Isa A.; Noor A.Y.M.; Samsudin A.Z.; Nizah M.A.M.; Azzis M.S.A. (Hampstead Psychological Associates, 2024)
Indexed by Scopus/ERA